Material Story in Narrative Architecture: Capturing Dialogue Between Material and Nature - Suryantini, Rini; Putri, Irfany Roihana; Atmodiwirjo, Paramita (International Journal of Built Environment and Scientific Research, 2025)
This paper discusses how material story constructs narrative architecture by emphasizing the dynamic dialogue between material and its surroundings. It argues that a story embedded within a material can hold greater importance than its physical form, providing a basis for developing narrative architecture. When material is viewed as something alive, its journey becomes important to study. The story acts as a vehicle to reveal the nature of a material, including the hidden one, allowing other agencies to be part of the story. Focusing on brick materiality as a case study, this paper examines how material responses emerge through interactions between the brick and nature. Based on the grouping of the responses, four material-nature dialogues can be categorized: patterning, reflecting, growing, and nesting. This analysis demonstrates that material story allows materiality to be interpreted narratively, generating multiple stories as a basis for scenarios within narrative architecture, enriching the architectural design process.